Hypertrophic Olivary Degeneration and Palatal or Oculopalatal Tremor - Tilikete, Caroline; Desestret, Virginie (Frontiers in Neurology, 2017)
Hypertrophic degeneration of the inferior olive is mainly observed in patients developing palatal or oculopalatal tremor. This syndrome manifests as a synchronous tremor of the palate (palatal tremor) and/or eyes (oculopalatal tremor) that may also involve other muscles from the branchial arches. It is associated with hypertrophic inferior olivary degeneration that is characterized by enlarged and vacuolated neurons, increased number and size of astrocytes, severe fibrillary gliosis and demyelination. It appears on MRI as an increased T2/FLAIR signal intensity and enlargement of the inferior olive. There are two main conditions in which hypertrophic degeneration of the inferior olive occurs. The most frequent, studied and reported condition is the development of palatal/oculopalatal tremor and hypertrophic degeneration of the inferior olive in the weeks or months following a structural brainstem or cerebellar lesion. This “symptomatic” condition requires a destructive lesion in the Guillain-Mollaret pathway, which spans from the contralateral dentate nucleus via the brachium conjunctivum and the ipsilateral central tegmental tract innervating the inferior olive. The most frequent etiologies of destructive lesion are stroke (hemorrhagic more often than ischemic), brain trauma, brainstem tumors, and surgical or gammaknife treatment of brainstem cavernoma. The most accepted explanation for this symptomatic palatal/oculopalatal tremor is that denervated olivary neurons released from inhibitory inputs enlarge and develop sustained synchronized oscillations. The cerebellum then modulates/accentuates this signal resulting in abnormal motor output in the branchial arches. In a second condition, palatal/oculopalatal tremor and progressive cerebellar ataxia occurs in patients without structural brainstem or cerebellar lesion, other than cerebellar atrophy. This syndrome of progressive ataxia and palatal tremor may be sporadic or familial. In the familial form, where hypertrophic degeneration of the inferior olive may not occur (or not reported), the main reported etiologies are Alexander disease, polymerase gamma (POLG) mutation and spinocerebellar ataxia type 20 (SCA20). Whether or not these are associated with specific degeneration of the dentato-olivary pathway remains to be determined. The most symptomatic consequence of oculopalatal tremor is eye oscillations. Therapeutic trials suggest gabapentin or memantine as valuable drugs to treat eye oscillations in oculopalatal tremor.